2022
DOI: 10.1186/s12889-022-14644-1
|View full text |Cite
|
Sign up to set email alerts
|

An analysis on the roles and involvements of different stakeholders in the provision of adolescent sexual and reproductive health services in Southeast Nigeria

Abstract: Introduction Sexual and reproductive health of young people involve a lot of stakeholders, traverse different sectors, and cut across all levels of government. For a clearer understanding of the activities of these stakeholders in adolescent sexual and reproductive health (ASRH) services, this paper was designed to explore the positions, attitudes and involvements of government/public institutions and non-governmental organizations (NGOs) in ASRH policy-making processes and implementations in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Since most sites had begun DTG roll-out before WHO recommended DTG to all, we hypothesise our observation is mostly related to the challenges in DTG access when tied to contraceptive use [3]. Indeed, contraceptive uptake among adolescent girls and young women in Sub-Saharan Africa is low [19,20] and healthcare providers lack education or face bias [21,22]. There is an urgent need to integrate sexual and reproductive health, including contraception and pregnancy planning into adolescent HIV care.…”
Section: Discussionmentioning
confidence: 99%
“…Since most sites had begun DTG roll-out before WHO recommended DTG to all, we hypothesise our observation is mostly related to the challenges in DTG access when tied to contraceptive use [3]. Indeed, contraceptive uptake among adolescent girls and young women in Sub-Saharan Africa is low [19,20] and healthcare providers lack education or face bias [21,22]. There is an urgent need to integrate sexual and reproductive health, including contraception and pregnancy planning into adolescent HIV care.…”
Section: Discussionmentioning
confidence: 99%
“…Over six million people reside in Ebonyi state, with about 40% tagged as adolescents (Agu et al ., 2022; Ebonyi State Government, 2023). A survey analysis of Ebonyi State reported that sexual debut among adolescents in Ebonyi state occur between 13 and 15 years (Mbachu et al ., 2020b), and of adolescents who are sexually active, about 10% of adolescent females have begun child bearing, with over 35% of them facing mortality incidents (Agu et al ., 2022; Ajah et al ., 2015). This led the Government of Ebonyi State to map specific local government areas (LGAs) in high need for SRH interventions (Mbachu et al ., 2020a).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that the state has a high maternal mortality rate (602 per 100,000 population), and 39.7% of these mortalities occur among adolescent girls aged 15–19 years. Further description of the study area can be found in our previously published papers [ 10 , 29 31 ].…”
Section: Methodsmentioning
confidence: 99%